Demographics and Client Satisfaction on the Establishment of Driver’s License Renewal Office - Donato, Noreen Grace D.; Ramos, Jelyn A. (Future Science / FSH-PH Publications, 2023)
This research study is an effort to determine the relationship between demographics and client satisfaction on the establishment of Driver’s License Renewal Offices. A Purposive Sampling survey method was utilized in collecting data using a revised Client Survey Questionnaire based on the Land Transportation Office Client Satisfaction Measurement Survey Form. The demographics of respondents were taken into account in terms of gender and age bracket. This research study utilized the Descriptive Statistics and Hypothesis Testing using the P-Value approach in deriving the conclusion that there is no significant difference on Demographics and Client Satisfaction and the Land Transportation office should support the program of establishing additional Driver’s License Renewal Offices nationwide. Furthermore, this study has come to the conclusion that the majority of the clients at Driver’s License Renewal Offices have a high level of client satisfaction and demographics do not have a high contributing factor on assessing the level of client satisfaction. Regardless of sex and age, an efficient service delivery can be recognized and acknowledged.